2020
DOI: 10.1101/2020.07.15.20154690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The First Consecutive 5000 Patients with COVID-19 in Qatar; a Nation-wide Cohort Study

Abstract: Background There are limited data on Coronavirus Disease 2019 (COVID-19) outcomes at a national level, and none after 60 days of follow up. The aim of this study was to describe national, 60-day all-cause mortality associated with COVID-19, and to identify risk factors associated with admission to an intensive care unit (ICU). Methods This was a retrospective cohort study including the first consecutive 5000 patients with COVID-19 in Qatar who completed 60 days of follow up by June 17, 2020. Outcomes included… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
3
9
2
Order By: Relevance
“…In addition to increasing age and male gender, these studies identified as risk factors, CKD [21,22] and cancer [21], but also DM and/or obesity [21,10,23,22], HT and/or CHD/CVD [21,23,22]. Two studies in Qatar and Kuwait, specifically focusing on ICU admission, stressed the increased risk associated with DM [24], in contrast with our results, findings in the literature are quite heterogeneous. Actually, meta-analyses found that DM was associated with higher risk of composite event combining ICU admission with mortality and/or severe/critical form of the disease [25,26,27], while other meta-analyses found an absence of increased ICU risk [28,29] or the evidence inconclusive [30].…”
Section: Results Derived From the Modelscontrasting
confidence: 90%
“…In addition to increasing age and male gender, these studies identified as risk factors, CKD [21,22] and cancer [21], but also DM and/or obesity [21,10,23,22], HT and/or CHD/CVD [21,23,22]. Two studies in Qatar and Kuwait, specifically focusing on ICU admission, stressed the increased risk associated with DM [24], in contrast with our results, findings in the literature are quite heterogeneous. Actually, meta-analyses found that DM was associated with higher risk of composite event combining ICU admission with mortality and/or severe/critical form of the disease [25,26,27], while other meta-analyses found an absence of increased ICU risk [28,29] or the evidence inconclusive [30].…”
Section: Results Derived From the Modelscontrasting
confidence: 90%
“…In a subsequent report in which the first 5000 patients with COVID-19 infection in Qatar were followed for up to 60 days after diagnosis, a total of 1424 patients (28.5%) required hospitalisation, out of which 108 (7.6%) were admitted to an intensive care unit (ICU), 14 patients (0.28%) had died, 10 (0.2%) were still in hospital and 2 (0.04%) were still in ICU. 21 …”
Section: Resultsmentioning
confidence: 99%
“…In a subsequent report in which the first 5000 patients with COVID-19 infection in Qatar were followed for up to 60 days after diagnosis, a total of 1424 patients (28.5%) required hospitalisation, out of which 108 (7.6%) were admitted to an intensive care unit (ICU), 14 patients Open access (0.28%) had died, 10 (0.2%) were still in hospital and 2 (0.04%) were still in ICU. 21 Google mobility reports data demonstrated a significant decrease in number of people visiting retail and recreation outlets, grocery and pharmacy stores, parks, transit stations and workplaces over time (table 5). A concurrent increase in people staying in residential areas was observed over this timeframe.…”
Section: Between 5 February 2020 and 18mentioning
confidence: 99%
“…Near three quarter (19) were hospitalized, counting one in intensive care unit (ICU), and altogether were discharged within the follow up dated. Nearby one third (10) pregnant women with coronavirus delivered throughout the follow up period; altogether had fit newborns with negative SARS-CoV-2 tests (Omrani, et al, 2020). In this context, primary studies propose that the infection is not transmitted from the mother to newborn by placental transmission or through discharges in the genital area.…”
Section: Discussionmentioning
confidence: 99%